The Impact of Creative Leadership on Strategic Agility in Startups: Mediating Roles of Resource Management and Innovative Work Behavior - Robertus Adi Nugroho; Bernardus Aris Ferdinan; Jessica Angelia Rosyadi (Business Review and Case Studies, 2024)
Background: Startups in Jakarta face significant challenges in adapting rapidly to a dynamic and competitive business environment. Understanding the role of Creative Leadership (CL) in fostering Strategic Agility (SA) is crucial for addressing these challenges.Purpose: This study aims to analyze the impact of Creative Leadership on Strategic Agility within Jakarta startups, with Innovative Work Behavior (IWB) and Creative Resource Management (CRM) acting as mediating variables.Design/Methodology/Approach: A total of 219 mid- to senior-level managers from various startups in Jakarta participated as respondents. The study utilized Smart PLS 4 as an analytical tool to examine the relationships among Creative Leadership, IWB, CRM, and Strategic Agility.Finding/Result: The findings revealed that Creative Leadership had a positive and significant impact on both Innovative Work Behavior (IWB) and Creative Resource Management (CRM). Additionally, IWB and CRM significantly mediated the relationship between Creative Leadership and Strategic Agility. This indicated that Creative Leadership not only directly enhanced organizational adaptability but also established a crucial foundation for innovation and creative resource management.Conclusion: The study underscores the importance of Creative Leadership in promoting Strategic Agility through the mediating effects of IWB and CRM. These results provide valuable insights for startup leaders and practitioners on optimizing creative leadership, stimulating innovative work behavior, and building responsive resource management strategies.Originality/Value (State of the Art): This study contributes to the theoretical understanding of the intricate relationships within the startup context. By involving a significant sample and employing sophisticated analytical tools, it offers practical guidance for developing strategic policies and actions that support the growth and sustainability of startups in a dynamic business environment. Keywords: creative leadership, strategic agility, start-up management, innovative work behavior, reative resource management